2012
DOI: 10.1111/j.1600-0722.2012.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on growth and metabolism of Streptococcus mutans

Abstract: Streptococcus mutans is a key contributor to dental caries. Smokers have a higher number of caries-affected teeth than do nonsmokers, but the association among tobacco, nicotine, caries, and S. mutans growth has not been investigated in detail. Seven S. mutans strains--UA159, UA130, 10449, A32-2, NG8, LM7, and OMZ175--were used in the present study. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC), planktonic cell growth, biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(184 citation statements)
references
References 34 publications
13
170
0
1
Order By: Relevance
“…In the present study, nicotine was demonstrated to stimulate S. gordonii biofilm formation and planktonic growth, which means nicotine is a preferred environmental factor for S. gordonii. Nicotine has a similar stimulation effect on S. mutans biofilm formation, but it has no effect or even reduces S. mutans planktonic cell growth (8). One bacterial nicotinic acetylcholine receptor (nAChR) homologue, which is a prokaryotic protongated ion channel, has been found in several bacterial species (21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, nicotine was demonstrated to stimulate S. gordonii biofilm formation and planktonic growth, which means nicotine is a preferred environmental factor for S. gordonii. Nicotine has a similar stimulation effect on S. mutans biofilm formation, but it has no effect or even reduces S. mutans planktonic cell growth (8). One bacterial nicotinic acetylcholine receptor (nAChR) homologue, which is a prokaryotic protongated ion channel, has been found in several bacterial species (21).…”
Section: Discussionmentioning
confidence: 98%
“…Overnight-grown S. gordonii cells were diluted 1:100 in TSB plus 1% sucrose (TSBS) with 0, 0.25, 0.5, 1, 2, and 4 mg/ml nicotine. Triplicate samples were grown in a sterile 96-well flat-bottom microtiter plate for 24 h. Biofilm formation was determined by a crystal violet assay described previously (8). Briefly, biofilm was fixed with formaldehyde, stained with crystal violet, and washed twice with saline to remove unbound crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…mutans strain UA159 (ATCC 700610) was used due to its completely sequenced genome. 9,10,16 The strain was stored at -80°C in tryptic soy broth (TSB, Acumedia, Baltimore, MA) with 20% glycerol until used. Mitis Salivarius Sucrose Bacitracin (MSSB, Anaerobe Systems, Morgan Hill, CA) agar plates were used to initially grow the strains.…”
Section: Materials and Methods Bacterial Strain And Growth And Antibimentioning
confidence: 99%
“…9 Carbohydrates in biofilm are metabolized by bacteria, producing lactic acid which causes dissolution of minerals, calcium and phosphate from teeth. 9,10,5 A fall in plaque pH caused by bacterial fermentation of carbohydrates causes a shift in the equilibrium concentration, leading to enamel erosion. 3 Acid production is considered one of the most important events in the pathogenesis of dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance was measured using a spectrophotometer (Spectramax 190, Molecular Devices, Sunnyvale, CA) at 490 nm that provides quantitative information on the relative density of the biofilm cells exposed to Violet-blue light and without Violet-blue light [17]. The biofilm assay experiments were repeated independently more than three times with similar results and one representative experiment is reported.…”
Section: Microtiter Plate Biofilm Assaymentioning
confidence: 99%